Distinguishing immunorelated haemocytopenia from idiopathic cytopenia of undetermined significance (ICUS): a bone marrow abnormality mediated by autoantibodies. (9th July 2014) - Fu, R; Liu, H; Wang, Y; Liu, H; He, H; Chen, J; Wang, H; Yu, H; Ding, K; Huang, L; Wang, H; Xing, L; et al.
Summary: In recent years we have observed that some patients with idiopathic cytopenia of undetermined significance (ICUS) responded well to corticosteroid and high-dose intravenous immunoglobulin treatment, indicating that some cytopenia in ICUS might be mediated by autoantibodies. In this study, we analysed 166 ICUS cases retrospectively, some of which were autoantibodies detected on haemopoietic cells in bone marrow (BM) by BM mononuclear cell (BMMNC)-Coombs test, flow cytometry (FCM), Western blot and immunofluorescence (IF). We found that 25·9% (43 of 166) of the cases had autoantibodies positive verified with BMMNC-Coombs test or FCM analysis, 72·1% (31 of 43) of whom had immunoglobulin (Ig)G autoantibody positive by Western blot. IgG could be detected in the erythroblastic islands on the BM smear of nine (32·1%, nine of 28) ICUS patients with autoantibodies by IF. Of these 43 patients, the median percentage of reticulocytes was 1·79%. More than half the patients had hyper-BM cellularity with a higher percentage of nucleated erythroid cells in the sternum. Total response rates to immunosuppressive therapy at 6, 12, 24 and > 36 months were 46·5% (20 of 43), 75% (30 of 40), 77·4% (24 of 31) and 66·7% (16 of 24), respectively. We termed this group of ICUS cases with autoantibodies as immunorelated haemocytopenia (or BMMNC-Coombs test-positive haemocytopenia).